2020
DOI: 10.25077/vj.9.1.12-17.2020
|View full text |Cite
|
Sign up to set email alerts
|

Experiences Around the Clauses: A Transitivity Analysis of Four Famous People’s Suicide Notes

Abstract: Four suicide notes written by three famous people, Jiah Khan, Kevin Carter, and Virginia Woolf, were analyzed in this study. Systemic Functional Linguistics theory especially about transitivity proposed by Halliday is used to see the ideational meaning of all four suicide notes by identifying the elements of the clauses. This study was conducted with a qualitative method assisted by a descriptive statistical method to see the spread and functions of the elements of transitivity in the suicide notes. To analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The results of the analysis of this article found 177 participants, as actors 26.55% and in the process, there were 103 materials, there were 44.67%, in the last findings circumstance was found as many as 80, with a percentage of 30%. Sawirman and Ridhwani (2020) wrote entitled experiences around the clauses: a transitivity analysis of four famous people's suicide notes. This article analysed transitivity analysis of four suicide letters from three suspected terrorists.…”
Section: Phenomenonmentioning
confidence: 99%
“…The results of the analysis of this article found 177 participants, as actors 26.55% and in the process, there were 103 materials, there were 44.67%, in the last findings circumstance was found as many as 80, with a percentage of 30%. Sawirman and Ridhwani (2020) wrote entitled experiences around the clauses: a transitivity analysis of four famous people's suicide notes. This article analysed transitivity analysis of four suicide letters from three suspected terrorists.…”
Section: Phenomenonmentioning
confidence: 99%
“…Furthermore, transitivity was used as a tool to reveal the intersection of language and psychology. Sawirman & Ridhwani (2020) utilize the framework of systemic functional linguistics to analyze the clauses in the suicide notes written by four famous people. They found that the frequent use of material processes indicates the writers' focus on their actions and the emotional involvement they experienced during the process of suicide.…”
Section: Transitivity As a Text-analysis Toolmentioning
confidence: 99%
“…Ridwani and Sawirman (2020) also have discussed a transitivity framework to identify and explain the ideational meaning of several letters by identifying the elements of each clause. Recent evidence suggests that the transitivity system is the key point to describe language meta-function (Sawirman and Ridhwani 2020). Fitri, et.al.…”
Section: Introductionmentioning
confidence: 99%